ESENSI ALAM SEMESTA DALAM PERSPEKTIF FALSAFAH PENDIDIKAN ISLAM - Nisa, Rafika (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2018)
This article describes the essence of the universe which is part of the ontological foundation in Islamic education. The ontological foundation is a thought about the origin of the events of the universe, from which and in which direction the process of events took place. And in the article will specialize the discussion of the essence of the universe in the perspective of Islamic education philosophy developed into the concept of the universe in the Koran, the process of creating the universe, the purpose of creating the universe, ways of understanding the universe and its implications for Islamic education. With the aim that this paper will increase human knowledge about the nature of the universe for humans.